P.S. you're the worst : a novel - Seager, Chloe (William Morrow, an imprint of HarperCollinsPublishers, 2025)
"Everyone knows the death card in a tarot reading isn't a literal death sentence. Well, everyone except Becky. Becky is not doing well. Her dreaded thirtieth birthday is looming, and she can't help thinking she's falling behind in life. Her (smug) friends are all planning weddings, buying houses, or starting their own businesses, but not Becky. She still lives with her mom, hates her job, doesn't speak to her father, and--despite numerous dates--hasn't moved on from her ex-boyfriend. Things can't get much worse. Becky doesn't believe in the arcane, but armed with a gift card and a desperate need for guidance, she visits a tarot reader ... who tells her she's going to die. Convinced she's a goner and panicked about having done nothing with her life, Becky finally takes action. She writes a series of letters to the people she loves unloading all the things she's been holding back. And she waits. But in the morning, she's not dead. And worse, the mail is already reaching people's doorsteps. Will the letters be the wake-up call Becky needs, or just the next step in a never-ending downward spiral?"--